2021
DOI: 10.1111/tpj.15432
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene‐activated MdPUB24 mediates ubiquitination of MdBEL7 to promote chlorophyll degradation in apple fruit

Abstract: SUMMARY Chlorophyll (Chl) degradation is a natural phenomenon that occurs during ripening in many fleshy fruit species, and also during fruit storage. The plant hormone ethylene is a key factor in promoting Chl degradation during fruit storage, but the mechanisms involved in this induction are largely unknown. In this study, an apple (Malus domestica) BEL1‐LIKE HOMEODOMAIN transcription factor 7 (MdBEL7), potentially functioning as a transcriptional repressor of the Chl catabolic genes (CCGs), including MdCLH,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…A characteristic paradigm was the transcription factors (TFs) PaBEL1H1; Pav_sc0000713.1_g640.1.mk and PaBEL1H9; Pav_sc0001794.1_g370.1.mk of ME27 that regulate chloroplast development and chlorophyll synthesis [ 35 ]. These TFs may influence PaBEL1H7; Pav_sc0001518.1_g260.1.mk of ME30 ( Figure 4 C) that were found to be involved in the chlorophyll degradation via ethylene production during fruit ripening [ 36 ]. The ME30 was characterized by the presence of FERONIA receptors since four of them (PaFERL; Pav_sc0000661.1_g020.1.br; Pav_sc0000681.1_g020.1.br; Pav_sc0004547.1_g070.1.br; Pav_sc0004547.1_g060.1.br) were contained in this module.…”
Section: Resultsmentioning
confidence: 99%
“…A characteristic paradigm was the transcription factors (TFs) PaBEL1H1; Pav_sc0000713.1_g640.1.mk and PaBEL1H9; Pav_sc0001794.1_g370.1.mk of ME27 that regulate chloroplast development and chlorophyll synthesis [ 35 ]. These TFs may influence PaBEL1H7; Pav_sc0001518.1_g260.1.mk of ME30 ( Figure 4 C) that were found to be involved in the chlorophyll degradation via ethylene production during fruit ripening [ 36 ]. The ME30 was characterized by the presence of FERONIA receptors since four of them (PaFERL; Pav_sc0000661.1_g020.1.br; Pav_sc0000681.1_g020.1.br; Pav_sc0004547.1_g070.1.br; Pav_sc0004547.1_g060.1.br) were contained in this module.…”
Section: Resultsmentioning
confidence: 99%
“…Overexpressing the barley JuBEL1 in tobacco resulted in the phenomenon of reduced male fertility [ 90 ]. Apple MdBEL7 was degraded by ubiquitination, with the U-box E3 ubiquitin ligase MdPUB24, resulting in the degradation of chlorophyll in apple during storage [ 57 ]. In tomato, SIBEL11 and SlBL4 have been shown to be involved in regulating the development of chloroplasts and chlorophyll synthesis in tomato fruit [ 40 , 41 ] ( Figure 2 ).…”
Section: The Function Of Blhs In Regulating Plant Developmentmentioning
confidence: 99%
“…In addition to transcriptional regulation, post-translational modifications play an important role in the regulatory network of transcription factors. Recent studies have shown that an E3 ubiquitin ligase (MdPUB24) in apple promotes the degradation of MdBEL7 and regulates the greening process of the apple fruit [ 57 ]. However, there are few studies on the post-translational modification of BLHs.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…A recent study showed that PUB25 and PUB26 positively regulated the cold-stress response by mediating MYB15 protein degradation [ 81 ]. In apples, MdPUB24 and MdPUB29 regulate fruit quality [ 82 , 83 ]. In addition, MdPUB29 may also be involved in the regulation of the plant immune response to fungal pathogens [ 84 ].…”
Section: Introductionmentioning
confidence: 99%